Agama Pada Masa Usia Lanjut - Sri Aqilah Maulida (Tarbawi, 2025)
This study aims to explain the role of religion in the elderly and how religion encourages them to live a life full of gratitude. This study emphasizes how religion plays a crucial role in the lives of the elderly, providing significant emotional, spiritual, and social support. The research methodology used is qualitative research using a library study approach, analyzing various literature such as relevant books and journals. The results of the study indicate that religion is not just an obligation, but a source of peace, and a deep meaning of life in old age. Therefore. understanding and support for the spiritual development of the elderly is very important to achieve optimal religious maturity and improve their quality of life. What needs to be of concern to all of us is the spiritual aspect in the care and support of the elderly, so that they can live their old age more meaningfully and full of hope.